ANALISIS PRODUKSI DAN KEBUTUHAN BERAS DI SULAWESI UTARA - Abraham Ch. Wowor; Oktavianus Porajouw; Gene H.M. Kapantow; Celsius Talumingan (Universitas Sam Ratulangi, 2014)
ABSTRACTRice production of North Sulawesi province in recent years has increased , but it can not compensate for the increase in demand for rice due to the increase in population and per capita consumption of rice. Therefore, until now North Sulawesi is still a deficit-rice region and this2affects the achievement of self-sufficiency in rice. The objective of research is to determine the conditions of production and the needs of current and projected rice production and rice needs in period 2012-2030 . The data used in this study is time series data from 1996 to 2011. Population growth , crop area , production and productivity . are analyzed descriptively using the table , the tool used in data processing program is Microsoft Excel 2007 .The result of the research showed that development of production and demand for rice in North Sulawesi fluctuated from year to year tend to increase very year . During the 16th -year period of North Sulawesi still could not cover the needs of rice .projection and production and need for rice in North Sulawesi at the average population growth of 1.42 percent per year during the 2012-2030 was deficit .the average population growth of 1.28 percent per year in 2012-2020 North Sulawesi is still in deficit despite the declining rice and this area will be self-sufficient in rice in 2025-2030. While of the average population growth of 1,1 percent per year of the next 19th years, North Sulawesi would have a rice surplus.